ULK1 methylation promotes TGF‐β1‐induced endometrial fibrosis via the FOXP1/DNMT1 axis - Yuhua Zeng; Qing Feng (Kaohsiung Journal of Medical Sciences)
Abstract Intrauterine adhesion (IUA) is the second most common cause of secondary infertility in women and can also lead to menstrual abnormalities and multiple adverse pregnancy outcomes. Therefore, elucidating the mechanism of its development is crucial for the prevention and treatment of IUA. This study will investigate the function and mechanism of forkhead box P1 (FOXP1)/DNA methyltransferase 1 (DNMT1)/unc‐51‐like autophagy activating kinase 1 (ULK1) in IUA. Expression levels of key genes were detected using western blot and quantitative ‐ real time reverse transcription polymerase chain reaction. Cell proliferation was detected by CCK‐8 and EdU staining. Transcriptional regulation relationships were detected by dual luciferase reporter gene and chromatin immunoprecipitation (ChIP) assay. Methylation station of ULK1 was detected by methylmion specific PCR (MSP). Fibrosis and pathological changes in the uterine cavity tissues were detected by Masson and hematoxylin and eosin staining. It was observed that the expression of FOXP1 and DNMT1 increased in transforming growth factor (TGF)‐β1‐induced cells, while ULK1 expression decreased. Downregulation of FOXP1 could inhibit human endometrial stromal cells proliferation and autophagy, as well as decrease the expression of fibrogenic factors (collagen type I alpha 1 chain [COL1A1], fibronectin [FN], and alpha‐smooth muscle actin [α‐SMA]). The results of MSP and ChIP experiments showed that DNMT1 promotes methylation of the ULK1 promoter region and inhibits its transcription. In an animal model, knockdown of FOXP1 alleviated pathological fibrosis and uterine adhesions. Knockdown of FOXP1 can inhibit endometrial fibrosis in IUA rats; FOXP1 could be a potential target for the treatment of IUA.